Synthesis, characterization and in vitro biocompatibility study of Au/TMC/Fe3O4 nanocomposites as a promising, nontoxic system for biomedical applications - Shirazi, Hanieh; Daneshpour, Maryam; Kashanian, Soheila; Omidfar, Kobra (Beilstein Journal of Nanotechnology, 2015)
The unique properties and applications of iron oxide and Au nanoparticles have motivated researchers to synthesize and optimize a combined nanocomposite containing both. By using various polymers such as chitosan, some of the problems of classic core–shell structures (such as reduced saturation magnetization and thick coating) have been overcome. In the present study, chitosan and one of its well-known derivatives, N-trimethylchitosan (TMC), were applied to construct three-layer nanocomposites in an Au/polymer/Fe3O4 system. It was demonstrated that replacement of chitosan with TMC reasonably improved the properties of the final nanocomposites including their size, magnetic behavior and thermal stability. Moreover, the results of the MTT assay showed no significant cytotoxicity effect when the Au/TMC/Fe3O4 nanocomposites were applied in vitro. These TMC-containing magnetic nanoparticles are well-coated by Au nanoparticles and have good biocompatibility and can thus play the role of a platform or a label in various fields of application, especially the biomedical sciences and biosensors.
Keywords: Au/polymer/Fe3O4 nanocomposites; Au nanoparticles; cell viability; magnetic nanoparticles; N-trimethyl chitosan

(untitled) - Lee, J.; Mahendra, S.; Alvarez, P. J. J. (ACS Nano, 2010)

(untitled) - Demming, A.; Österbacka, R.; Han, J.-W. (Nanotechnology, 2014)

(untitled) - Yang, D.; Hartman, M. R.; Derrien, T. L.; Hamada, S.; An, D.; Yancey, K. G.; Cheng, R.; Ma, M.; Luo, D. (Acc. Chem. Res., 2014)

(untitled) - Mélinon, P.; Begin-Colin, S.; Duvail, J. L.; Gauffre, F.; Herlin Boime, N.; Ledoux, G.; Plain, J.; Reiss, P.; Silly, F.; Warot-Fonrose, B. (Phys. Rep., 2014)

(untitled) - Buzea, C.; Pacheco, I. I.; Robbie, K. (Biointerphases, 2007)

(untitled) - Mody, V. V.; Siwale, R.; Singh, A.; Mody, H. R. (J. Pharm. BioAllied Sci., 2010)

(untitled) - Ahmadi, A.; Shirazi, H.; Pourbagher, N.; Akbarzadeh, A.; Omidfar, K. (Mol. Biol. Rep., 2014)

(untitled) - Omidfar, K.; Zarei, H.; Gholizadeh, F.; Larijani, B. (Anal. Biochem., 2012)

(untitled) - Gao, G.; Shi, R.; Qin, W.; Shi, Y.; Xu, G.; Qiu, G.; Liu, X. (J. Mater. Sci., 2010)

(untitled) - Omidfar, K.; Kia, S.; Larijani, B. (Hybridoma, 2011)

(untitled) - Yen, S. K.; Padmanabhan, P.; Selvan, S. T. (Theranostics, 2013)

(untitled) - Hao, R.; Xing, R.; Xu, Z.; Hou, Y.; Gao, S.; Sun, S. (Adv. Mater., 2010)

(untitled) - Maity, D.; Chandrasekharan, P.; Yang, C.-T.; Chuang, K.-H.; Shuter, B.; Xue, J.-M.; Ding, J.; Feng, S.-S. (Nanomedicine (London, U. K.), 2010)

(untitled) - Li, C.; Li, L.; Keates, A. C. (Oncotarget, 2012)

(untitled) - Zhang, Z.; Wang, X.; Yang, X. (Analyst, 2011)

(untitled) - Yu, L.; Wu, H.; Wu, B.; Wang, Z.; Cao, H.; Fu, C.; Jia, N. (Nano-Micro Lett., 2014)

(untitled) - Akbarzadeh, A.; Mikaeili, H.; Zarghami, N.; Mohammad, R.; Barkhordari, A.; Davaran, S. (Int. J. Nanomed., 2012)

(untitled) - Akbarzadeh, A.; Samiei, M.; Davaran, S. (Nanoscale Res. Lett., 2012)

(untitled) - Wu, W.; He, Q.; Jiang, C. (Nanoscale Res. Lett., 2008)

(untitled) - Faraji, M.; Yamini, Y.; Rezaee, M. (J. Iran. Chem. Soc., 2010)

(untitled) - Song, Y.; Wang, Y.; Ji, S.; Ding, J. (Nano-Micro Lett., 2012)

(untitled) - Jokerst, J. V.; Lobovkina, T.; Zare, R. N.; Gambhir, S. S. (Nanomedicine (London, U. K.), 2011)

(untitled) - Veiseh, O.; Gunn, J. W.; Zhang, M. (Adv. Drug Delivery Rev., 2010)

(untitled) - Laurent, S.; Forge, D.; Port, M.; Roch, A.; Robic, C.; Vander Elst, L.; Muller, R. N. (Chem. Rev., 2008)

(untitled) - Podrepšek, G. H.; Knez, Ž.; Leitgeb, M. (J. Nanopart. Res., 2013)

(untitled) - Yalçıner, F.; Çevik, E.; Şenel, M.; Baykal, A. (Nano-Micro Lett., 2011)

(untitled) - Tafaghodi, M.; Saluja, V.; Kersten, G. F. A.; Kraan, H.; Slütter, B.; Amorij, J.-P.; Jiskoot, W. (Vaccine, 2012)

(untitled) - Moghassemi, S.; Parnian, E.; Hakamivala, A.; Darzianiazizi, M.; Vardanjani, M. M.; Kashanian, S.; Larijani, B.; Omidfar, K. (Mat. Sci. Eng. C, 2015)

(untitled) - Cao, X.; Ye, Y.; Liu, S. (Anal. Biochem., 2011)

(untitled) - Dykman, L. A.; Khlebtsov, N. G. (ActaNaturae, 2011)

(untitled) - Omidfar, K.; Khorsand, F.; Darziani Azizi, M. (Biosens. Bioelectron., 2013)

(untitled) - Zeng, S.; Yu, X.; Law, W.-C.; Zhang, Y.; Hu, R.; Dinh, X.-Q.; Ho, H.-P.; Yong, K.-T. (Sens. Actuators, B, 2013)

(untitled) - Gole, A.; Murphy, C. J. (Chem. Mater., 2004)

(untitled) - Smolensky, E. D.; Neary, M. C.; Zhou, Y.; Berquo, T. S.; Pierre, V. C. (Chem. Commun., 2011)

(untitled) - Gregorio-Jauregui, K. M.; Pineda, M. G.; Rivera-Salinas, J. E.; Hurtado, G.; Saade, H.; Martinez, J. L.; Ilyina, A.; López, R. G. (J. Nanomater., 2012)

(untitled) - Ishizaka, T.; Ishigaki, A.; Kawanami, H.; Suzuki, A.; Suzuki, T. M. (J. Colloid Interface Sci., 2012)

(untitled) - Mahmoudi, M.; Sant, S.; Wang, B.; Laurent, S.; Sen, T. (Adv. Drug Delivery Rev., 2011)

(untitled) - Chen, S.-P.; Yu, X.-D.; Xu, J.-J.; Chen, H.-Y. (Biosens. Bioelectron., 2011)

(untitled) - de Britto, D.; de Assis, O. B. G. (Int. J. Biol. Macromol., 2007)

(untitled) - Dung, D. T. K.; Hai, T. H.; Long, B. D.; Truc, P. N. (J. Phys.: Conf. Ser., 2009)

(untitled) - Qiu, Y.; Ma, Z.; Hu, P. (J. Mater. Chem. A, 2014)

(untitled) - Robinson, I.; Tung, L. D.; Maenosono, S.; Wälti, C.; Thanh, N. T. K. (Nanoscale, 2010)

(untitled) - Darwish, M. S. A.; Peuker, U.; Kunz, U.; Turek, T. (J. Mater. Sci., 2011)

(untitled) - Salehizadeh, H.; Hekmatian, E.; Sadeghi, M.; Kennedy, K. (J. Nanobiotechnol., 2012)

(untitled) - Belessi, V.; Zboril, R.; Tucek, J.; Mashlan, M.; Tzitzios, V.; Petridis, D. (Chem. Mater., 2008)

(untitled) - Mohammad, F.; Arfin, T. (Adv. Mater. Lett., 2014)

(untitled) - Naqvi, S.; Samim, M.; Abdin, M. Z.; Ahmed, F. J.; Maitra, A. N.; Prashant, C. K.; Dinda, A. K. (Int. J. Nanomed., 2010)

(untitled) - Vijayakumar, S.; Ganesan, S. (J. Nanomater., 2012)

(untitled) - Wang, H.; Shrestha, T. B.; Basel, M. T.; Dani, R. K.; Seo, G.-M.; Balivada, S.; Pyle, M. M.; Prock, H.; Koper, O. B.; Thapa, P. S.; Moore, D.; Li, P.; et al. (Beilstein J. Nanotechnol., 2012)

(untitled) - Kayal, S.; Ramanujan, R. V. (J. Nanosci. Nanotechnol., 2010)

(untitled) - Vongchan, P.; Wutti-In, Y.; Sajomsang, W.; Gonil, P.; Kothan, S.; Linhardt, R. J. (Carbohydr. Polym., 2011)

(untitled) - Sajomsang, W.; Tantayanon, S.; Tangpasuthadol, V.; Daly, W. H. (Carbohydr. Polym., 2008)

(untitled) - Mourya, V. K.; Inamdar, N. N. (J. Mater. Sci.: Mater. Med., 2009)

(untitled) - Babič, M.; Horák, D.; Lukash, L. L.; Ruban, T. A.; Kolomiets, Y. N.; Shpylova, S. P.; Grypych, O. A. (Beilstein J. Nanotechnol., 2014)